Kepastian Hukum Penerapan Kriteria Kewenangan Penyidikan Perkara Tindak Pidana Korupsi oleh Komisi Pemberantasan Korupsi Republik Indonesia - Lambertus Josua Tallaut; Ade Adhari (Universitas Pendidikan Nasional, 2022)
Corruption crimes at the investigation stage, the authority is owned by the Prosecutor's Office, the Police, and the KPK. The authority of the KPK is regulated in Article 11 of the KPK Law. However, in practice, the Prosecutor's Office investigates corruption cases that fall under the authority of the KPK, which results in legal uncertainty. The purpose of this research is to understand the essence of legal certainty, and its application is related to the authority to investigate the KPK normatively, as well as to be investigated by the Attorney General's Office. The type of research used is juridical-empirical, the research approach is the law approach and the case approach. Certainty is a legal value that underlies the birth of legal principles and norms, therefore it must be upheld because the consequences are goals rather than law. The prosecutor's action in investigating the corruption case is the authority of the KPK to create legal uncertainty, which means it violates the value of legal certainty. The prosecutor's reasoning that Article 11 is just a norm is clearly not true, because Article 11 is part of a strategic criminal law formulation policy and also the case investigated by the Prosecutor's Office caused problems because it did not file an appeal against the decision of PT DKI Jakarta which was considered to have violated the sense of justice. Prosecutors' actions violate the value of legal certainty, injure the characteristics of the rule of law and injure the strategic city of criminal law policies at the formulation stage.